A comparative study of shear bond strength of three different bracket bases bonded to porcelain surfaces - Trakyalı, Göksu; Sınmazışık, Gülden (Marmara Dental Journal, 2013)
Previous studies showed that the bonding strength of brackets to porcelain restorations and the failure model depend on many variables including bracket base design. The aim of this in-vitro study was to investigate Shear Bond Strength (SBS) of different bracket base designs on porcelain surfaces and to evaluate the sites of adhesive fracture with the Adhesive Remnant Index (ARI). Sixty feldspathic porcelain discs were randomly divided into three different groups each of twenty. Maxillary right incisor metal brackets with three different base designs (Victory series, 3M Unitek, Monrovia, California; Dyna-Lock, 3M Unitek, Monrovia, California and Mini Topic, Dentaurum, Inspringen, Germany) were bonded on the deglazed and conditioned porcelain surfaces in group 1, 2 and 3 respectively. Brackets were debonded and SBS was calculated in Mega Pascal (MPa). ARI scores were recorded after debonding. SBS forces calculated for group 1, 2 and 3 were 20,57 (± 7,18), 16,84 (± 6,20), 18,55 (± 5,46) MPa respectively. ANOVA and Multiple Comparison test revealed no significant difference in ARI scores between groups. Porcelain fractures after debonding were observed in groups 1 and 3. All brackets tested provided acceptable SBS. However, only Dyna-Lock brackets did not cause any porcelain fractures at debonding. This finding could be an acceptable reason to use this kind of brackets during orthodontic treatment of patient having porcelain restorations.
Keywords: Orthodontics, bracket base, dental porcelain, shear bond strength.